I learned that a Hermitian matrix $A$ is defined as a matrix that satisfies $$A^\dagger=(A^*)^\intercal=A,$$ i.e. its Hermitian conjugate $A^\dagger$ is the same as the original matrix $A$.

I also learned that in QM, a Hermitian operator $H$ is defined as an operator that satisfies $$ \langle f|Hg\rangle=\langle Hf|g\rangle,$$ where $f$ and $g$ are vectors.

Since operators and matrix can be represented by matrices in a particular basis, how can it be shown that a Hermitian matrix with the property $(A^*)^\intercal=A$ also satisfies $ \langle f|Ag\rangle=\langle Af|g\rangle$?


$\langle f|Ag\rangle=\langle f|A|g\rangle$.

$\langle Af|g\rangle$:

  • $(\langle Af|) = (|Af\rangle)^\dagger =(A|f\rangle)^\dagger = \langle f |A^\dagger$,
  • so $\langle Af|g\rangle = \langle f |A^\dagger|g\rangle$

If $A = A^\dagger$, then $\langle f|Ag\rangle =\langle Af|g\rangle$.

  • 4
    $\begingroup$ in infinite dimensional spaces there are subtleties of domain etc... $\endgroup$ – ZeroTheHero Jun 21 '20 at 2:24
  • $\begingroup$ Hi :-) I think that there is a missing symbol here: $\langle f |A^\dagger$ into your answer. Best regards. $\endgroup$ – Sebastiano Jun 21 '20 at 10:35

In matrix form, $$\langle f|Ag\rangle = f^\dagger A g,$$ $$\langle Af|g\rangle= (Af)^\dagger g.$$

Using the matrix property of $(AB)^\dagger=B^\dagger A^\dagger$ on the latter expression, we get $$\langle Af|g\rangle = (Af)^\dagger g=f^\dagger A^\dagger g.$$

Hence if $A=A^\dagger$, then $$\langle Af|g\rangle= f^\dagger A^\dagger g= f^\dagger A g=\langle f|Ag\rangle.$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.